New Insight into Titanium–Magnesium Ziegler–Natta Catalysts Using Photoluminescence Spectroscopy - Panchenko, Valentina N. (Appl Spectrosc, 2020)
This paper presents the results of study of titanium–magnesium catalysts often used in polymerization processes, by photoluminescence spectroscopy (PL) in combination with diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). The interaction of dibutyl phthalate (DBP) with MgCl(2) was studied at DBP(added)/Mg = 0–1 (mol/mol). The luminescence spectra with excitation at 278 nm and the excitation spectra for main emission bands were recorded. It was shown that DBP adsorbed on magnesium chloride, both in the form of donor–acceptor complexes (D(+)A(–)) and in the form of molecular complexes. At DBP(added)/Mg <0.15, the formation of D(+)A(–) complexes occur predominantly; with an increase in DBP(added)/Mg, the fraction of molecular complexes increases. Molecular complexes are destroyed during the treatment of the support by TiCl(4). In this case, the structure of magnesium chloride is disordered and new coordination–unsaturated sites are formed. This work is a first attempt to apply PL spectroscopy in combination with DRIFTS spectroscopy to study titanium–magnesium Ziegler–Natta catalysts. The application of PL spectroscopy to such systems made it possible to detect interactions within and between donor molecules, which would be particularly challenging to achieve using other spectroscopic methods. Both spectroscopic methods provided crucial information about the existence of two types of complexes on the sample surface which is important for tuning the synthesis procedure of the titanium–magnesium catalysts for olefin polymerization.